Tubular zinc negative electrode of zinc-air battery and preparation method of tubular zinc negative electrode
By using the preparation method of tubular zinc negative electrode in zinc air batteries, the poor electrochemical reversibility of traditional zinc foil negative electrodes and the drying of plate negative electrodes are solved, and higher cycle stability and discharge capacity are achieved.
Patent Information
- Application Number
- CN202510151813.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-25
AI Technical Summary
The traditional zinc foil negative electrode of zinc air batteries has problems such as poor electrochemical reversibility, easy passivation, limited capacity output and shortened cycle life. The plate negative electrode is prone to cracking and de-alia during drying, affecting the discharge efficiency and stability of the battery.
Using the preparation method of tubular zinc negative electrode, the zinc powder, zinc oxide powder and dopant are dried and added conductive agent, fibers and binder, and ultrasonic dispersed and inserted into the paste extrusion tube between the grid bar and the sleeve to form a compact zinc paste structure and curing it in a constant temperature and humidity box.
It effectively alleviates the dendrite and deformation problems of zinc negative electrode during the reaction process, improves the cycle stability and discharge capacity of the negative electrode of the battery, reduces the risk of short circuit of the battery and shortens the service life.
Smart Images

Figure CN119890239A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air batteries and preparation thereof, and in particular relates to a tubular zinc negative electrode of a zinc-air battery and a preparation method thereof. Background Art
[0002] Zinc-air batteries, with their high energy density, lightweight design, economical cost-effectiveness and excellent safety, have shown great potential for application in the field of energy storage systems and power equipment. With the continuous advancement of science and technology, zinc-air batteries are actively exploring the expansion of applications in mobile electronic devices, portable devices and electric vehicle industries, aiming to lead a new round of innovation in new energy technologies.
[0003] However, the negative electrode materials used in zinc-air batteries in practical applications still have some defects. Traditionally, zinc foil is used as the negative electrode, but this material has a significant problem of poor electrochemical reversibility. During the battery discharge process, the zinc foil negative electrode is prone to passivation, which not only severely limits the battery's capacity output, but also leads to a significant reduction in cycle life, becoming the main bottleneck restricting the widespread commercial application of zinc-air batteries.
[0004] In order to overcome the limitations of zinc foil negative electrodes, existing improvements generally involve mixing the active material and the adhesive evenly, coating them on the surface of the current collector, and drying them to form a plate-type negative electrode. The purpose of this design is to improve the discharge capacity and rate performance of the battery and to improve the overall performance of the battery by optimizing the negative electrode structure. Nevertheless, the plate-type negative electrode is prone to cracking and de-paste during the drying process, which may not only lead to leakage of the electrolyte, but also directly affect the discharge efficiency and stability of the battery.
[0005] What is more complicated is that the zinc negative electrode generates products such as zinc oxide and zinc hydroxide during discharge, which have good solubility in strong alkaline electrolytes. During the charging process, when the zinc oxide or zinc hydroxide on the electrode is completely reduced to metallic zinc, the zincate ions in the electrolyte tend to undergo reduction reactions on the raised parts of the electrode surface, and then form dendritic zinc deposits, namely zinc dendrites, along the diffusion path of the zincate ions. The formation of zinc dendrites is often inconsistent with the dissolution area, resulting in uneven distribution of active substances on the electrode surface, which in turn causes deformation of the zinc negative electrode. This series of changes will eventually lead to a decrease in battery capacity, shortened cycle life, and even premature battery failure.
[0006] In addition, the zinc paste of the plate-type negative electrode is directly exposed to the electrolyte and lacks the necessary structural support, which makes it very easy to form zinc dendrites and deformation during the charge and discharge cycle, and even cause the active material to fall off and accumulate. These phenomena not only increase the risk of short circuit of the battery, but also seriously affect the stability and service life of the battery. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art, provide a tubular zinc negative electrode for a zinc-air battery, effectively alleviate problems such as dendrites and deformation of the negative electrode during the reaction process, effectively improve the problem of battery failure caused by short circuit of the battery negative electrode, and improve the battery cycle stability. The present invention also provides a preparation method thereof.
[0008] The method for preparing the tubular zinc negative electrode of the zinc-air battery of the present invention comprises the following steps: (1) Preparation of zinc paste: dry-mix zinc powder, zinc oxide powder and dopant, add conductive agent and fiber, disperse by ultrasonic, add binder solution, stir and add water to adjust the apparent density of zinc paste, and obtain zinc paste; (2) Preparation of zinc negative electrode samples: insert a paste extrusion tube between the grid ribs and the sleeve, squeeze the zinc paste into the sleeve under a pressure of 50-70 kg, start squeezing the paste from the top of the plate, withdraw while squeezing, and finally pull the sleeve out from the end of the plate, add a plug at the end to make a zinc negative electrode sample; (3) The zinc negative electrode sample is solidified and dried to obtain a tubular zinc negative electrode for a zinc-air battery.
[0009] The curing procedure described in step (3) is as follows: first control the temperature between 15-30°C, the relative humidity between 20-40%, and the drying time for 4-6 hours, then control the drying temperature to 55-75°C, the relative humidity ≤2%, and continue drying for 20-30 hours.
[0010] The oxygen content of the zinc powder in step (1) is ≤0.1%, and the zinc oxide powder is nano-grade zinc oxide with a particle size between 1 and 100 nanometers.
[0011] Step (1) During the whole process, the temperature is controlled below 50°C, and the stirring time is ≥ 60 min. After the stirring is completed, the apparent density of the zinc paste is measured and adjusted to 4.5-6.5 g / cm 3 .
[0012] The conductive agent in step (1) is one or more of acetylene black, conductive carbon black, Super P, and carbon nanotubes.
[0013] The dopant in step (1) is one or more of indium oxide, bismuth oxide, and lead oxide.
[0014] The fiber in step (1) is one of polyester fiber, polyester fiber, glass fiber and polypropylene fiber.
[0015] The binder solution in step (1) is one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, sodium carboxymethyl cellulose, and aqueous polyurethane.
[0016] The grid ribs in step (2) are selected from the group consisting of carbon rods, Cu rods, Al rods, multi-element alloys, and MOF-based materials, and the surface of the ribs is electroplated with a zinc layer, the rib diameter is 2-6 mm, and the zinc coating thickness is 0.1-1 mm. The sleeve is a non-woven fabric or polyester fabric cut and sewn according to size.
[0017] A zinc-air battery tubular zinc negative electrode is prepared by the preparation method of the zinc-air battery tubular zinc negative electrode. The raw materials include, by weight: 65-85 parts of zinc powder, 5-25 parts of zinc oxide powder, 5-10 parts of binder solution, 0.2-6 parts of conductive agent, 0.1-3 parts of dopant, and 0.2-0.8 parts of fiber.
[0018] Specifically, the method for preparing the tubular zinc negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of zinc paste: During the entire stirring process, the temperature is controlled below 50°C. 65-85 parts of zinc powder, 5-25 parts of zinc oxide powder, and 0.1-3 parts of dopant are added to a small paste mixer for initial dry mixing. Stir for 30 minutes, then add 0.2-6 parts of conductive agent and 0.2-0.8 parts of fiber. Ultrasonic dispersion is performed for 30 minutes to mix evenly without agglomeration. Dry mix and stir again for 30 minutes. After observing that the powder is uniform and free of particles, 5-10 parts of binder solution are finally added. Stirring is continued. Deionized water is added to adjust the apparent density of the zinc paste to 4.5-6.5 g / cm 3 , get zinc paste.
[0019] (2) Preparation of zinc negative electrode samples: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 50-70 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a seal at the end to make a zinc negative electrode sample.
[0020] The grid bars are made of one or more materials such as carbon rods, Cu rods, Al rods, multi-element alloys, and MOF-based materials, and the surface of the bars is electroplated with zinc, the diameter of the bars is 2-6 mm, and the thickness of the zinc coating is 0.1-1 mm. The sleeve is made of non-woven fabric or polyester fabric cut and sewn according to size.
[0021] (3) The zinc negative electrode sample is placed in a constant temperature and humidity chamber for curing. The procedure is as follows: first control the temperature between 15-30°C and the relative humidity between 20-40% for 4-6 hours, then control the drying temperature to 55-75°C and the relative humidity ≤2%, and continue drying for 20-30 hours. After drying, a tubular zinc negative electrode of a zinc-air battery is obtained and the battery is assembled.
[0022] The present invention inserts a paste extrusion tube between the grid ribs and the sleeve, and then starts to squeeze the paste from the upper end of the pole plate, while squeezing and withdrawing, and finally extracts the sleeve from the end of the pole plate, squeezes it into the paste extrusion tube under pressure, the zinc paste is compacted inside, and the active material has a strong bonding force with the grid ribs. At the same time, compared with the plate-type zinc negative electrode, the tubular paste extrusion negative electrode has a strong ability to resist dendrites, deformation and shedding in actual use due to the wrapping protection of the sleeve, and the battery has obvious advantages. The conductive agent can not only play a conductive role, but also be randomly arranged and contacted with each other in the zinc paste during the mixing process, so that the electrode gap tortuosity coefficient is reduced, which is conducive to the diffusion and migration of zinc ions and hydroxide ions, thereby reducing the internal resistance of the electrode, and providing a diffusion channel for the electrolyte, thereby improving the discharge capacity of the battery. At the same time, the dopant has a high surface energy, and it is easy to interact with water molecules to form hydrogen bonds, so that the water molecules are attached to the surface of the dopant, showing hydrophilicity, making it easier for the electrolyte to diffuse into the electrode, which can effectively improve the utilization rate of the negative electrode active material, and then improve the battery capacity. Finally, the fiber can be used as the skeleton of the ion transmission channel and the connector between the negative electrode zinc paste to improve the ion transmission efficiency and structural stability of the zinc negative electrode, which can effectively reduce the cracking and shedding of the electrode when it is dried, thereby improving the discharge performance and cycle performance of the zinc-air battery. In order to solve the problems of deformation, dendrites, and shedding of the zinc negative electrode, it is wrapped with a non-woven fabric or polyester fabric sleeve and compacted under a certain pressure. However, after compaction, it is difficult for the electrolyte to enter, the reaction is difficult, and the utilization rate of the active material is low. Therefore, conductive agents, dopants, and fiber additives are added to solve the problem of low utilization of active materials.
[0023] In the present invention, the zinc negative electrode is solidified in a constant temperature and humidity device after the paste is extruded, so that the temperature and humidity can be strictly controlled, so that the zinc paste is better combined with the grid ribs, and the problem of cracking and falling off of the negative electrode when drying is effectively alleviated. In addition, the prepared zinc negative electrode is found in experiments to better inhibit the growth of zinc dendrites, increase the discharge capacity of the negative electrode, and improve the reversibility of zinc deposition / dissolution.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The zinc-air battery tubular zinc negative electrode prepared by the method of the present invention can reduce the internal resistance of the electrode, improve the electrochemical reversibility of the zinc negative electrode, increase the utilization rate of the tubular negative electrode active material, and increase the discharge capacity of the zinc-air battery by improving the zinc paste formula.
[0025] (2) The method for preparing the tubular zinc negative electrode of the zinc-air battery of the present invention has the advantages of being environmentally friendly and requiring little investment in environmental protection, and is convenient for realizing the automated production of the extruded zinc negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the cycle life diagram of battery 1# prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with specific embodiments.
[0028] The raw materials and additives used below are all commercially available products. The weight parts mentioned are based on the same unit of mass.
[0029] The oxygen content of the zinc powder used below is ≤0.1%, and the zinc oxide powder is nano-grade zinc oxide with a particle size between 1-100 nanometers.
[0030] The binder solutions used are all commercially available products with a solid content of 60%.
[0031] Example 1 The method for preparing the tubular zinc negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of zinc paste: During the entire stirring process, the temperature was controlled below 50°C. 85 parts of zinc powder, 5 parts of zinc oxide powder, and 2.8 parts of indium oxide were added to a small paste mixer for initial dry mixing. The mixture was stirred for 30 minutes. Then, 2 parts of acetylene black and 0.2 parts of polyester fiber were added. The mixture was ultrasonically dispersed for 30 minutes to ensure uniform mixing without agglomeration. The mixture was dry mixed again for 30 minutes. After the powder was observed to be uniform and free of particles, 5 parts of polytetrafluoroethylene binder solution were finally added. Deionized water was added while stirring. The final zinc paste had an apparent density of 4.5 g / cm 3 .
[0032] (2) Preparation of zinc negative electrode samples: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 60 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a seal at the end to make a zinc negative electrode sample.
[0033] The grid bars are carbon rods with surface electrogalvanized, the diameter of the carbon rods is 4 mm, and the thickness of the zinc coating is 1 mm. The sleeves are non-woven fabrics cut and sewn according to size.
[0034] (3) The zinc negative electrode sample was placed in a constant temperature and humidity chamber for curing. The procedure was as follows: first, the temperature was controlled at 22°C, the relative humidity was 30%, and the drying time was 5 h. Then, the drying temperature was controlled at 60°C, the relative humidity was ≤2%, and the drying was continued for 25 h. After drying, a tubular zinc negative electrode of a zinc-air battery was obtained. The battery was assembled and numbered 1#.
[0035] The cycle life of the prepared 1# battery is shown in the figure Figure 1 As shown in the figure, it can be seen that the tubular negative electrode formed by squeezing the zinc paste into the casing under pressure has good stability due to the compact internal structure of the zinc paste and the casing binding the outside of the plate. After running for more than 280 hours, the zinc utilization rate is still maintained at 94.9%. This shows that the zinc-air battery prepared by this method has high power density and long cycle life.
[0036] Example 2 The method for preparing the tubular zinc negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of zinc paste: The temperature was controlled below 50°C during the entire stirring process. 65 parts of zinc powder, 25 parts of zinc oxide powder, and 1 part of bismuth oxide were added to a small paste mixer for initial dry mixing. The mixture was stirred for 30 minutes. Then 3.2 parts of conductive carbon black and 0.8 parts of polyester fiber were added. The mixture was ultrasonically dispersed for 30 minutes to ensure uniform mixing without agglomeration. The mixture was dry mixed again for 30 minutes. After the powder was observed to be uniform and free of particles, 5 parts of polyvinylidene fluoride binder solution were finally added. Deionized water was added while stirring. The final zinc paste had an apparent density of 5 g / cm 3 .
[0037] (2) Preparation of zinc negative electrode samples: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 50 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a plug at the end to make a zinc negative electrode sample.
[0038] The grid bars are Cu rods which are electro-galvanized on the surface, the diameter of the Cu rods is 4 mm, and the thickness of the zinc coating is 1 mm. The sleeves are polyester cloth cut and sewn according to the size.
[0039] (3) The zinc negative electrode sample was placed in a constant temperature and humidity chamber for curing. The procedure was as follows: first, the temperature was controlled at 15°C, the relative humidity was 20%, and the drying time was 6 hours. Then, the drying temperature was controlled at 55°C, the relative humidity was ≤2%, and the drying was continued for 30 hours. After drying, a tubular zinc negative electrode of a zinc-air battery was obtained. The battery was assembled and numbered 2#.
[0040] Example 3 The method for preparing the tubular zinc negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of zinc paste: The temperature was controlled below 50°C during the entire stirring process. 75 parts of zinc powder, 15 parts of zinc oxide powder, and 0.1 parts of lead oxide were added to a small paste mixer for initial dry mixing. The mixture was stirred for 30 minutes. Then 0.2 parts of Super P and 0.5 parts of glass fiber were added. The mixture was ultrasonically dispersed for 30 minutes to ensure uniform mixing without agglomeration. The mixture was dry mixed again for 30 minutes. After the powder was observed to be uniform and free of particles, 9.2 parts of polyvinyl alcohol binder solution were added. Deionized water was added while stirring. The final zinc paste had an apparent density of 6.5 g / cm 3 .
[0041] (2) Preparation of zinc negative electrode samples: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 70 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a seal at the end to make a zinc negative electrode sample.
[0042] The grid bars are Al rods with surface electrogalvanizing, the Al rods have a diameter of 4 mm, and the thickness of the zinc coating is 1 mm. The sleeves are non-woven fabrics cut and sewn according to size.
[0043] (3) The zinc negative electrode sample was placed in a constant temperature and humidity chamber for curing. The procedure was as follows: first, the temperature was controlled at 30°C, the relative humidity was 40%, and the drying time was 4 h. Then, the drying temperature was controlled at 75°C, the relative humidity was ≤2%, and the drying was continued for 20 h. After drying, a tubular zinc negative electrode of a zinc-air battery was obtained. The battery was assembled and numbered 3#.
[0044] Example 4 The method for preparing the tubular zinc negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of zinc paste: During the entire stirring process, the temperature was controlled below 50°C. 75 parts of zinc powder, 5.8 parts of zinc oxide powder, 1.5 parts of indium oxide and 1.5 parts of bismuth oxide were mixed and added to a small paste mixer for initial dry mixing. The mixture was stirred for 30 min. Then, 3 parts of acetylene black, 3 parts of carbon nanotubes and 0.2 parts of polypropylene fiber were added. Ultrasonic dispersion was performed for 30 min to mix evenly without agglomeration. The mixture was dry mixed and stirred again for 30 min. After the powder was observed to be uniform and free of particles, 10 parts of sodium carboxymethyl cellulose binder solution were finally added. Deionized water was added while stirring. The final zinc paste had an apparent density of 4.5 g / cm 3 .
[0045] (2) Preparation of zinc negative electrode samples: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 60 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a seal at the end to make a zinc negative electrode sample.
[0046] The grid bars are made of multi-element alloy and are electro-galvanized on the surface, the diameter of the multi-element alloy is 4 mm, and the thickness of the zinc coating is 1 mm. The sleeve is made of polyester cloth cut and sewn according to size.
[0047] (3) The zinc negative electrode sample was placed in a constant temperature and humidity chamber for curing. The procedure was as follows: first, the temperature was controlled at 30°C, the relative humidity was 30%, and the drying time was 5 h. Then, the drying temperature was controlled at 60°C, the relative humidity was ≤2%, and the drying was continued for 25 h. After drying, a tubular zinc negative electrode of a zinc-air battery was obtained. The battery was assembled and numbered 4#.
[0048] Example 5 The method for preparing the tubular zinc negative electrode of the zinc-air battery comprises the following steps: (1) Preparation of zinc paste: During the entire stirring process, the temperature was controlled below 50°C. 65 parts of zinc powder, 10 parts of zinc oxide powder, 1.5 parts of indium oxide and 1.5 parts of lead oxide were mixed and added to a small paste mixer for initial dry mixing. The mixture was stirred for 30 minutes. Then 3 parts of acetylene black, 3 parts of Super P and 0.8 parts of polyester fiber were added. Ultrasonic dispersion was performed for 30 minutes to mix evenly without agglomeration. The mixture was dry mixed and stirred again for 30 minutes. After the powder was observed to be uniform and free of particles, 10 parts of aqueous polyurethane binder solution were finally added. Deionized water was added while stirring. The final zinc paste had an apparent density of 5 g / cm 3 .
[0049] (2) Preparation of zinc negative electrode samples: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 70 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a seal at the end to make a zinc negative electrode sample.
[0050] The grid bars are made of MOF-based materials and are electrogalvanized on the surface. The diameter of the MOF-based materials is 4 mm and the thickness of the zinc coating is 1 mm. The sleeve is made of non-woven fabrics cut and sewn according to size.
[0051] (3) The zinc negative electrode sample was placed in a constant temperature and humidity chamber for curing. The procedure was as follows: first, the temperature was controlled at 22°C, the relative humidity was 30%, and the drying time was 5 h. Then, the drying temperature was controlled at 60°C, the relative humidity was ≤ 2%, and the drying was continued for 25 h. After drying, a tubular zinc negative electrode of a zinc-air battery was obtained. The battery was assembled and numbered 5#.
[0052] Comparative Example 1 The method for preparing the zinc negative electrode comprises the following steps: Preparation of zinc paste: 85 parts of zinc powder, 2 parts of zinc oxide powder and 3 parts of indium oxide were added to a small paste machine for initial dry mixing, and the stirring time was 30 minutes; then 2 parts of acetylene black and 1 part of polyester fiber were added, and the acetylene black and polyester fiber were first ultrasonically dispersed for 30 minutes, and the mixture was required to be uniform and without agglomeration; dry mixing was fully stirred for another 30 minutes. After observing that the powder was uniform and without particles, 7 parts of polytetrafluoroethylene binder solution were finally added, and stirring was continued until the zinc paste was prepared. The temperature was controlled below 50°C during the entire stirring process.
[0053] Preparation of zinc negative electrode: Weigh the prepared zinc paste according to the designed load value, and then apply the zinc paste on the treated galvanized copper mesh by pressing and flattening to make the zinc negative electrode. Put the zinc negative electrode into a constant temperature and humidity curing kiln for curing. The curing procedure is as follows: control the temperature to 80°C and continue drying for 40 hours. After the zinc negative electrode is dried, assemble the battery for standby use, numbered 6#.
[0054] Comparative Example 2 2mm thick zinc plate, after surface grinding, acetone degreasing, deionized water cleaning, 60℃ drying, assembled battery standby, numbered 7#.
[0055] Comparative Example 3 The method for preparing the zinc negative electrode comprises the following steps: (1) Preparation of zinc paste: Add 85 parts of zinc powder and 5 parts of zinc oxide powder to a small paste mixer for dry mixing and stirring for 30 minutes; then add 2 parts of conductive carbon black and 1 part of polyester fiber. First, ultrasonically disperse the conductive carbon black and polyester fiber for 30 minutes. The mixture should be uniform and free of agglomerates; then dry mix and stir for another 30 minutes. After observing that the powder is uniform and free of particles, add 7 parts of polytetrafluoroethylene binder solution and continue stirring until the zinc paste is prepared. The temperature should be controlled below 50°C during the entire stirring process.
[0056] (2) Preparation of zinc negative electrode: Weigh the prepared zinc paste according to the designed load value, insert a paste extrusion tube between the grid ribs and the sleeve, and then squeeze it into the sleeve under a pressure of 60 kg. Start squeezing the paste from the top of the plate, withdrawing it while squeezing, and finally pull out the sleeve from the end of the plate. Add a seal at the end to make the zinc negative electrode.
[0057] The grid bars are carbon rods with surface electrogalvanized, the diameter of the carbon rods is 4 mm, and the thickness of the zinc coating is 1 mm. The sleeves are non-woven fabrics cut and sewn according to size.
[0058] (3) Place the zinc negative electrode in a constant temperature and humidity chamber for curing. The procedure is as follows: control the temperature to 80°C and continue drying for 40 hours. After the zinc negative electrode is dried, assemble the battery for standby use and number it 8#.
[0059] The 1-8# batteries prepared in the above embodiments and comparative examples were tested using a common electrode test method, and an electrochemical workstation was used to perform impedance testing and LSV testing. The test results are shown in Table 1.
[0060] Table 1 Electrochemical workstation test results
[0061] As can be seen from Table 1, the addition of conductive agent, dopant and fiber has a certain influence on the battery impedance, but the influence is far less than the influence of the amount of active material added and the pressure of extrusion. By comparing Example 1 and Example 4, it can be seen that under the same extrusion pressure, the more active material, the smaller the impedance and the greater the power; by comparing Example 3 and Example 4, it can be seen that under the same conditions of zinc powder, the more conductive agent is added, the lower the resistance. The reason for this is that the conductive agent contacts each other during the mixing process of zinc paste, which is conducive to the diffusion and migration of zinc ions and hydroxide ions, thereby reducing the internal resistance of the electrode. By comparing Example 1 and Comparative Example 1, it can be seen that the difference in the preparation methods of coated plate and extruded paste has a greater impact on the battery impedance performance, and the maximum power of the extruded paste negative electrode is 58.5mW higher than that of the coated plate negative electrode, indicating that the performance of the negative electrode prepared by extrusion is better; by comparing Example 1 and Comparative Example 3, it can be seen that the negative electrode without dopant has a large impedance and low power, proving that the addition of dopant has a positive effect on the performance of the negative electrode.
[0062] The 1-8# batteries prepared in the above embodiments and comparative examples were subjected to constant current charge and discharge tests using an Arbin charger and discharger. The test results are shown in Table 2.
[0063] Table 2 Charge and discharge test results
[0064] As can be seen from Table 2, the discharge capacity of Examples 1-5 prepared by the present invention is good. By comparing Example 1 with Comparative Example 1, it can be seen that the discharge capacity of the negative electrode prepared by squeezing the paste is much greater than that of the coated plate negative electrode, whether it is a large current or a small current, indicating that the preparation method of squeezing the paste improves the discharge capacity of the negative electrode and increases the utilization rate of the negative electrode active material. By comparing Example 1 with Comparative Example 3, it can be seen that the addition of the dopant increases the hydrophilicity of the negative electrode, and the electrolyte is more likely to enter the interior of the electrode, thereby generating an electrochemical reaction, thus proving that the dopant is beneficial to improving the discharge capacity of the negative electrode. By comparing Example 3 with Example 4, it can be found that, under the same zinc powder situation, the greater the pressure of squeezing the paste, the greater the discharge capacity is reduced, the greater the pressure of squeezing the paste, the higher the compactness of the zinc paste, and the electrode is less likely to react, so it is necessary to add an appropriate amount of additives to improve the discharge capacity of the battery.
[0065] The 1-8# batteries prepared in the above examples and comparative examples were subjected to cycle life tests using an Arbin charge-discharge machine. The test results are shown in Table 3. The test results of Example 1 are shown in Figure 1 .
[0066] Table 3 Cycle life test results
[0067] As can be seen from Table 3, the number of cycles of Examples 1-5 prepared by the present invention is better. By comparing Example 1 with Comparative Example 1, it can be seen that the number of cycles of the negative electrode prepared by extruding the paste is 58 times more than that of the coated plate, indicating that the extruding paste preparation method improves the cycle life of the negative electrode. By comparing Example 3 with Example 4, it can be found that under the same zinc powder, the greater the extrusion pressure, the more cycles, and the greater the pressure, the smaller the degree of dendrite deformation of the negative electrode, which indicates that the main factors affecting the cycle life are the deformation and dendrites of the negative electrode. It can be seen from Example 1 and Comparative Example 2 that the cycle life of the zinc plate is 76 times less than that of the extruded paste negative electrode, indicating that the negative electrode prepared by extruding the paste can better inhibit the growth of zinc dendrites, improve the reversibility of zinc deposition / dissolution, and improve the discharge capacity and cycle life of the negative electrode.
Claims
1. A method for preparing a tubular zinc negative electrode for a zinc-air battery, characterized in that: The following steps are involved: (1) Preparation of zinc paste: dry-mix zinc powder, zinc oxide powder and dopant, add conductive agent and fiber, disperse by ultrasonic, add binder solution, stir and add water to adjust the apparent density of zinc paste, and obtain zinc paste; (2) Preparation of zinc negative electrode samples: insert a paste extrusion tube between the grid ribs and the sleeve, squeeze the zinc paste into the sleeve under a pressure of 50-70 kg, start squeezing the paste from the top of the plate, withdraw while squeezing, and finally pull the sleeve out from the end of the plate, add a plug at the end to make a zinc negative electrode sample; (3) The zinc negative electrode sample is solidified and dried to obtain a tubular zinc negative electrode for a zinc-air battery.
2. The method for preparing a zinc-air battery tubular zinc negative electrode according to claim 1, characterized in that: The curing procedure described in step (3) is as follows: first control the temperature between 15-30°C, the relative humidity between 20-40%, and the drying time for 4-6 hours, then control the drying temperature to 55-75°C, the relative humidity ≤2%, and continue drying for 20-30 hours.
3. The method for preparing a tubular zinc negative electrode for a zinc-air battery according to claim 1, characterized in that: The oxygen content of the zinc powder in step (1) is ≤0.1%, and the zinc oxide powder is nano-grade zinc oxide with a particle size between 1 and 100 nanometers.
4. The method for preparing a tubular zinc negative electrode for a zinc-air battery according to claim 1, characterized in that: Step (1) The temperature is controlled below 50°C during the whole process, and the stirring time is ≥60min. After the stirring is completed, the apparent density of the zinc paste is measured to be 4.5-6.5g / cm 3 .
5. The method for preparing a zinc-air battery tubular zinc negative electrode according to claim 1, characterized in that: The conductive agent in step (1) is one or more of acetylene black, conductive carbon black, Super P, and carbon nanotubes.
6. The method for preparing a tubular zinc negative electrode for a zinc-air battery according to claim 1, characterized in that: The dopant in step (1) is one or more of indium oxide, bismuth oxide, and lead oxide.
7. The method for preparing a tubular zinc negative electrode for a zinc-air battery according to claim 1, characterized in that: The fiber in step (1) is one of polyester fiber, polyester fiber, glass fiber and polypropylene fiber.
8. The method for preparing a tubular zinc negative electrode for a zinc-air battery according to claim 1, characterized in that: The binder solution in step (1) is one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl alcohol, sodium carboxymethyl cellulose, and aqueous polyurethane solution.
9. The method for preparing a tubular zinc negative electrode for a zinc-air battery according to claim 1, characterized in that: The grid ribs described in step (2) are one of carbon rods, Cu rods, Al rods, multi-element alloys, and MOF-based materials, and the surface of the ribs is electroplated with a zinc layer, the rib diameter is 2-6 mm, the zinc coating thickness is 0.1-1 mm, and the sleeve is a non-woven fabric or polyester fabric cut and sewn according to size.
10. A tubular zinc negative electrode for a zinc-air battery, characterized in that: The invention is prepared by the preparation method of the zinc-air battery tubular zinc negative electrode according to any one of claims 1 to 9, wherein the raw materials include, by weight: 65-85 parts of zinc powder, 5-25 parts of zinc oxide powder, 5-10 parts of binder solution, 0.2-6 parts of conductive agent, 0.1-3 parts of dopant, and 0.2-0.8 parts of fiber.